2011
DOI: 10.1260/2041-4196.2.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Analysis of Foam Cladding Protected Reinforced Concrete Slabs against Blast Loadings

Abstract: A AB BS ST TR RA AC CT T Protection of infrastructure against blast loading has been receiving more attention in recent years due to occasional engineering explosion accidents, e.g., chemical plant explosion, and intentional man-made explosions, e.g., rising terrorist attacks. An effective solution to mitigate blast effects on these buildings is to protect them with sacrificial foam claddings for absorption of blast energy. However, little research has been conducted to analyze the effectiveness of metallic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The simulated strain in the elastic phase seems to be smaller in comparison with the predicted strain, while a much longer extended plastic plateau for metallic foam is obtained in the numerical simulation. Moreover, the simulated densification strain is approximately around 60% which matches well with the value for aluminum foam (Wu et al 2011). Figure 7, from which it is observed that the deformation firstly concentrates on the one or two layers of weakest region of specimen.…”
Section: Development Of Microstructure Modelsupporting
confidence: 80%
See 1 more Smart Citation
“…The simulated strain in the elastic phase seems to be smaller in comparison with the predicted strain, while a much longer extended plastic plateau for metallic foam is obtained in the numerical simulation. Moreover, the simulated densification strain is approximately around 60% which matches well with the value for aluminum foam (Wu et al 2011). Figure 7, from which it is observed that the deformation firstly concentrates on the one or two layers of weakest region of specimen.…”
Section: Development Of Microstructure Modelsupporting
confidence: 80%
“…Recent research indicates that newly developed mobile and lightweight materials, such as metallic foams which have high capabilities to dissipate energy as they are cellular solids, are very attractive for use as cladding in applications for protection against external blasts (Wu et al 2010(Wu et al , 2011Sadot et al 2005). Newly developed lightweight materials such as honeycomb and aluminium foams exhibit special pore microstructures as shown in Figure 1 (Lu and Yu 2006) and have been widely used as good energy absorbing materials.…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
“…The numerical model used in the current research was based on field blast tests carried out by Zhu et al [23], whose blast testing data were previously used to validate a single degree of freedom model [24] and a simplified finite element model [25]. However, the accuracy of these models is relatively low.…”
Section: Materials Models In Ls-dynamentioning
confidence: 99%
“…Considerable research has been conducted on the study of protective structures aiming at reducing the transmitted pressure to the main structure. Sacrificial cladding structures receive a lot of attention [1][2][3][4][5][6][7][8][9][10]. They consist of a crushable core between the main structure and a front plate.…”
Section: Introductionmentioning
confidence: 99%
“…However, these cores are characterized by a relatively high plateau stress (between 1 and 10 MPa [14]) to protect a given structure. Wu and Zhou [9] study the use of foam cladding to protect a simply supported reinforced concrete (RC) slab against blast loading. They use an adapted SDOF model supported by a full scale experiment to study the effectiveness of aluminium foam on RC slab.…”
Section: Introductionmentioning
confidence: 99%